2020
DOI: 10.1016/j.jimonfin.2020.102183
|View full text |Cite
|
Sign up to set email alerts
|

Import prices and invoice currency: Evidence from Chile

Abstract: BIS Working Papers are written by members of the Monetary and Economic Department of the Bank for International Settlements, and from time to time by other economists, and are published by the Bank. The papers are on subjects of topical interest and are technical in character. The views expressed in them are those of their authors and not necessarily the views of the BIS. This publication is available on the BIS website (www.bis.org).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Compared to the earlier studies, our findings for Turkey's overall imports and exports are lower than those for developed countries, such as Canada (0.484 in Devereux et al, 2017) and New Zealand (0.475 in Fabling & Sanderson, 2015), for Chile (0.95 in Giuliano & Luttini, 2020), for developed (average import price passthrough = 0.60, average export price pass-through = 0.39), and emerging countries (average import price passthrough = 0.54, average export price pass-through = 0.51). However, they are higher than those for East Asian countries, including Indonesia, Malaysia, Philippines and Thailand (Parsons & Sato, 2006).…”
Section: Data and Descriptive Statisticscontrasting
confidence: 94%
See 1 more Smart Citation
“…Compared to the earlier studies, our findings for Turkey's overall imports and exports are lower than those for developed countries, such as Canada (0.484 in Devereux et al, 2017) and New Zealand (0.475 in Fabling & Sanderson, 2015), for Chile (0.95 in Giuliano & Luttini, 2020), for developed (average import price passthrough = 0.60, average export price pass-through = 0.39), and emerging countries (average import price passthrough = 0.54, average export price pass-through = 0.51). However, they are higher than those for East Asian countries, including Indonesia, Malaysia, Philippines and Thailand (Parsons & Sato, 2006).…”
Section: Data and Descriptive Statisticscontrasting
confidence: 94%
“…Similarly, both short‐ and long‐run pass‐through to import (export) prices is lower (higher) in developed than emerging countries, while pass‐through is affected by the share of the exporter's currency in invoicing. Giulino and Luttini (Giuliano & Luttini, 2020) concluded that choice of exporter currency against the U.S dollar affects medium‐term exchange rate pass‐through in Chile. Abdulqadir (2022) reported that depending on the real income, trade openness and terms of trade, there exist asymmetric pass‐through effect on the exporter's currency invoice in 44 sub‐Saharan African countries.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…The magnitude of this exchange rate pass-through depends, again, on country-specific macroeconomic characteristics, including the volatility of the exchange rate and the credibility of monetary policy (Ha et al, 2019). But, in spite of this heterogeneity, the vast majority of countries will experience some increase in inflation, with one-year passthrough estimates ranging from 0.05 all the way to 0.5 (Sopromadze et al, 2021;Giuliano and Luttini, 2019;Goldfajn and Werlang, 2000).…”
Section: International Spillovers Of Us Monetary Policymentioning
confidence: 99%
“…For Argentina and Colombia, I obtain the data from Gopinath (2016). For Chile, I obtain the data from Labbe (2018) and Giuliano and Luttini (2019). For Peru, I obtain the data from Castellares (2017).…”
Section: Real Exchangementioning
confidence: 99%
“…Exposure IndicesSource: Author's calculations based on national sources, BIS,Kamps (2006),Goldberg and Tille (2009),Gopinath (2016),Castellares (2017),Labbe (2018), andGiuliano and Luttini (2019).…”
mentioning
confidence: 99%